Diverse impacts of the rs58542926 E167K variant in TM6SF2 on viral and metabolic liver disease phenotypes. Issue 1 (30th March 2016) - Eslam, Mohammed; Mangia, Alessandra; Berg, Thomas; Chan, Henry Lik Yuen; Irving, William L.; Dore, Gregory J.; Abate, Maria Lorena; Bugianesi, Elisabetta; Adams, Leon A.; Najim, Mustafa A.M.; Miele, Luca; Weltman, Martin; et al.
Abstract : A genome‐wide exome association study has identified the transmembrane 6 superfamily member 2 ( TM6SF2 ) rs58542926 variant encoding an E167K substitution as a genetic determinant of hepatic steatosis in nonalcoholic fatty liver disease (NAFLD). The roles of this variant across a spectrum of liver diseases and pathologies and on serum lipids comparing viral hepatitis to NAFLD and viral load in chronic viral hepatitis, as well as its intrahepatic molecular signature, have not been well characterized. We undertook detailed analyses in 3260 subjects with viral and nonviral liver diseases and in healthy controls. Serum inflammatory markers and hepatic expression of TM6SF2 and genes regulating lipid metabolism were assessed in a subset with chronic hepatitis C (CHC). The rs58542926 T allele was more prevalent in 502 NAFLD patients than controls ( P = 0.02) but not different in cohorts with CHC (n = 2023) and chronic hepatitis B (n = 507). The T allele was associated with alterations in serum lipids and hepatic steatosis in all diseases and with reduced hepatic TM6SF2 and microsomal triglyceride transfer protein expression. Interestingly, the substitution was associated with reduced CHC viral load but increased hepatitis B virus DNA. The rs58542926 T allele had no effect on inflammation, impacted ≥F2 fibrosis in CHC and NAFLD assessed cross‐sectionally (odds ratio = 1.39, 95% confidence interval 1.04‐1.87, and odds ratio = 1.62, 95% confidence interval 1.03‐2.52, respectively; P < 0.03 for both), but had no effect on fibrosis progression in 1174 patients with CHC and a known duration of infection. Conclusion: The TM6SF2 E167K substitution promotes steatosis and lipid abnormalities in part by altering TM6SF2 and microsomal triglyceride transfer protein expression and differentially impacts CHC and chronic hepatitis B viral load, while effects on fibrosis are marginal. (Hepatology 2016;64:34–46)